Inność kulturowa w reportażach Ryszarda Kapuścińskiego i ich rosyjskich przekładach - Mocarz-Kleindienst, Maria (Acta Polono-Ruthenica, 2018)
Cultural otherness is an inherent feature of the literary genre of reportage. It is perceived as a cognitive value due to the presence of culturally marked elements. Hence, a preferable term is “otherness” than “strangeness”. Frequently, cultural otherness is accompanied by linguistic otherness, thanks to direct borrowings used both in source and translated texts. The subjects of perceiving and consciously creating otherness are the author of the reportage and the target reader projected by him, expecting to gain interesting information about the part of reality which is the object of the reporter’s description. In the process of translation, the translator also becomes an additional subject as the recipient of the source text and the author of the translation. The positive approach towards reception of otherness in Kapuścinski’s reportages as well as the way of presentation of such phenonema in the studied texts (through the use of explication) makes translators use exotisation as a well-thought-out strategy